Export expansion and labor market dynamics in Indonesia - Fajar Oktiyanto; Riandy Laksono; Yessi Vadila (Center for Indonesian Policy Studies (CIPS), 2024)
Does export expansion lead to improvements in labor market outcomes? The literature on this topic offers mixed insights. Despite the increasing importance of export markets, informality remains high and inequality continues to worsen in many developing economies. Additionally, export growth driven by commodities has been associated with the Dutch disease phenomenon. This study examines whether broader export expansion, including manufacturing exports alongside commodities, can positively impact labor market outcomes. Using Indonesia, a major commodity-dependent nation, as a case study, we analyze the effects of export expansion during the early 2000s, triggered by the import demand shock in China following its accession to the World Trade Organization (WTO). Our findings indicate that exposure to export expansion led to improvements in formal employment opportunities by 2014. However, the benefits to earnings growth are not uniform; they are observed only in specific cases. Notably, the export expansion episode appears relatively progressive, generating more formal employment opportunities and earnings growth for individuals in the lower- and middle-income brackets. By examining all tradable goods, we identify distinct impacts of different export categories. Our results suggest that the improvements in labor market outcomes are primarily driven by the expansion of manufacturing exports rather than commodities.
Keywords: F14; F16; F63; F66; J31; J46; 330; export; labor market; informal job; earnings; inequality; Indonesia; People's Republic of China (PRC)